Vertical Differentiation and Import Reducing Tariff - Luca Lambertini; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
Two monopolists operate in two countries which differ only for their per capita income. Each firm sells a single product which is vertically differentiated. If trade opens, the firm operating in the poorer country starts to export to the richer. This might induce the government of the richer country to set an import reducing tariff that could, under certain conditions, benefit also the firm of the poorer country.
Keywords: 330